How Crisis Management Strategies Address Stakeholders’ Sociocognitive Concerns and Organizations’ Social Evaluations - Iqbal, Farhan; Pfarrer, Michael D.; Bundy, Jonathan (Academy of Management Review, 2024)
Crises are harmful events that can influence organizational outcomes, leading to significant scholarly and practitioner interest in crisis management. A limitation of this line of inquiry, however, is that it typically glosses over stakeholders’ multiple concerns and the multiple factors that comprise organizations’ response strategies. To address this limitation, we delineate stakeholders’ crisis concerns into rational, emotional, and moral aspects. We then develop a typology along two dimensions of crisis response strategies—accountability and attention—to predict the likelihood that a specific strategy mitigates each of these concerns. We theorize that certain strategies mitigate just one type of concern, while others mitigate multiple concerns—albeit with a lower likelihood of success. Finally, we apply our typology to an organization’s social evaluations—i.e., important, proximal outcomes affected by a crisis—in order to better understand the tradeoffs associated with managing stakeholders’ multiple concerns.